Five-Year Follow-up of an Immediate Implant Placement in the Aesthetic Zone - Dhami, Bhageshwar; Shrestha, Priti (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Immediate implants are placed in the site of surgical extraction of the tooth to be replaced. The percentage success of such procedures varies among authors from 94-100%. Immediate implant placement is most commonly indicated when tooth extraction is done with pathologies not amenable to treatment. The advantages include reduced post-extraction alveolar bone resorption, shortened treatment time, and the avoidance of a second surgical intervention with regard to delayed implantation. This report describes a case of immediate implant placed in a maxillary central incisor followed by evaluation of soft and hard tissue changes occurring during post-operative period with a follow-up at five years.